Modeling Techniques and Stability Analysis Tools for Grid-Connected Converters - Peng Q.; Buticchi G.; Tan N.M.L.; Guenter S.; Yang J.; Wheeler P. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric impedance; Electric power system stability; Electric power transmission networks; Frequency domain analysis; Phase locked loops; Power converters; Power electronics; Time domain analysis; Grid-connected converters; Harmonic stability; Impedance; Impedance-based analyse; Model method; Model stability; Modelling techniques; Power systems stability; Stability analyze; Harmonic analysis